Jihadist Group's Criticism of Bassam Tibi's Thoughts - Permana, Dudi; Melyani, Mila; Alawiah, Neli (UIN Sunan Gunung Djati Bandung, 2025)
This study examines the ideological tension between Bassam Tibi's reformist Islamic thought and the responses of jihadist groups in Indonesia. The research aims to explore how these groups interpret Tibi’s rejection of the Islamic state and his call for contextual reinterpretation of Islamic teachings as a threat to the purity of Islam. Employing a qualitative descriptive approach and content analysis method, the study draws on primary sources, including Tibi’s works and jihadist writings, as well as secondary academic literature. The findings reveal that while Tibi promotes an ethical and contextual understanding of Islam aligned with democratic values, human rights, and pluralism, jihadist groups oppose these interpretations and perceive them as part of a Westernization agenda. They assert that Islam must remain a comprehensive system that includes political and military dimensions, rejecting secularism and reinterpretation as forms of deviation. This study concludes that the conflict between reformist and jihadist Islamic perspectives reflects a broader epistemological struggle within contemporary Islamic discourse. The research contributes to academic debate by offering a deeper understanding of the ideological contestation surrounding Islam and modernity. Furthermore, it emphasizes the need for a contextual and dialogical approach to Islamic teachings as a means to foster moderation and coexistence in plural societies.